Effects of nitrogen deposition on soil nitrogen fractions and enzyme activities in wet meadow of the Qinghai-Tibet Plateau - Jiangqi Wu; Haiyan Wang; Guang Li; Nan Chen (Scientific Reports)
Abstract Soil nitrogen (N) transformation is an essential portion of the N cycle in wetland ecosystems, governing the retention status of soil N by controlling the effective soil N content. N deposition produced by human activities changes the physical characteristics of soil, affecting N fractions and enzyme activities. To characterize these influences, three different N addition levels (N5, 5 g/m2; N10, 10 g/m2; N15, 15 g/m2) were established using a wet meadow on the Qinghai-Tibet Plateau (QTP) as a control treatment (0 g/m2). We investigated the features of soil physical property alterations, N fractions contents, and enzyme activities under N addition conditions throughout the peak plant growth season. Our findings indicated that N addition significantly enhanced soil aeration, porosity, total nitrogen (TN), ammonium nitrogen (NH4 +), nitrate nitrogen (NO3 −) content, and urease activity. At the same time, it decreased soil dissolved organic nitrogen (DON) content and bulk density (BD). Additionally, N addition treatment exerted a significant seasonal impact on soil nitrogen component content. The nitrogen component content within the surface soil (0–10 cm) under four treatments is more sensitive to N addition, whereas the nitrogen component in the deep soil is relatively stable. Principal component analysis demonstrated that soil aeration and porosity were the primary factors affecting soil N fractions and enzyme activities. The findings suggested that lower levels of N addition promoted the transformation process of soil N pools in wet meadows and exacerbated the loss of N in wetland ecosystems. Our findings indicate that sustained increases in N deposition will accelerate soil microbial N cycling, potentially overcoming N limitation in alpine wetland ecosystems and exacerbating the risk of N loss and greenhouse gas emissions from alpine wetland surface soils.